INSTITUTIONAL FACTORS OF WOMEN FARMER COOPERATIVES AND THEIR INFLUENCE ON ACCESS TO LOAN FROM MICROFINANCE BANKS IN SOUTHWEST NIGERIA (Journal of the Management Sciences, 2025)
This study investigates the institutional factors influencing women farmer cooperatives’ access to loans from microfinance banks in Southwest Nigeria. The specific objectives are to examine disparities between loan requests and actual access, evaluate the influence of organizational capacity, and assess the effect of safety-related qualities on loan approval. A descriptive and quantitative research design was employed, using a structured questionnaire and interview schedule to collect primary data from cooperative members in Lagos, Oyo, and Ogun States. A sample size of 370 respondents was determined using Taro Yamane’s formula. Data were analyzed using descriptive and inferential statistical techniques. Findings reveal significant gaps between requested and approved loan amounts, with an average shortfall of 18.5%, indicating that cooperatives frequently receive less funding than needed. This shortfall is linked to microfinance banks’ conservative lending practices, risk aversion, and strict eligibility criteria. Organizational capabilities—such as functional administrative structures, regular meetings, strategic planning, and effective conflict resolution—were found to significantly enhance loan access, reflected in a grand mean score of 4.73 on a 5-point Likert scale. Safety-related qualities, including membership size, credit experience, and collateral provision, also positively influenced loan approval, with a grand mean score of 4.70. The study recommends that cooperatives strengthen financial planning and risk management to mitigate funding gaps, while microfinance banks should balance risk considerations with the need to support agricultural development. Enhancing both organizational and safety qualities can improve cooperatives’ creditworthiness and access to essential financial resources, thereby fostering growth within the agricultural sector.
Keywords: Women farmer cooperatives; Microfinance banks; Loan access; Organizational capacity; Safety qualities; Institutional factors